Biophysical study of the non-steroidal anti-inflammatory drugs (NSAID) ibuprofen, naproxen and diclofenac with phosphatidylserine bilayer membranes (2016)
ABSTRACT: Non-steroidal anti-inflammatory drugs (NSAIDs) represent an effective pain treatment option and therefore one of the most sold therapeutic agents worldwide. The study of the molecular interactions responsible for their physiological activity, but also for their side effects, is therefore important. This report presents data on the interaction of the most consumed NSAIDs (ibuprofen, naproxen and diclofenac) with one main phospholipid in eukaryotic cells, dimyristoylphosphatidylserine (DMPS). The applied techniques are Fourier-transform infrared spectroscopy (FTIR), with which in transmission the gel to liquid crystalline phase transition of the acyl chains in the absence and presence of the NSAID are monitored, supplemented by differential scanning calorimetry (DSC) data on the phase transition. FTIR in reflection (ATR, attenuated total reflectance) is applied to record the dependence of the interactions of the NSAID with particular functional groups observed in the DMPS spectrum such as the ester carbonyl and phosphate vibrational bands. With Förster resonance energy transfer (FRET) a possible intercalation of the NSAID into the DMPS liposomes and with isothermal titration calorimetry (ITC) the thermodynamics of the interaction are monitored. The data show that the NSAID react in a particular way with this lipid, but in some parameters the three NSAID clearly differ, with which now a clear picture of the interaction processes is possible.